Epigenetic Modifications in Alzheimer’s Neuropathology and Therapeutics - Esposito, Michelle; Sherr, Goldie Libby (Frontiers in Neuroscience, 2019)
Transcriptional activation is a highly synchronized process in eukaryotes that requires a series of cis- and trans-acting elements at promoter regions. Epigenetic modifications, such as chromatin remodeling, histone acetylation/deacetylation, and methylation, have frequently been studied with regard to transcriptional regulation/dysregulation. Recently however, it has been determined that implications in epigenetic modification seem to expand into various neurodegenerative disease mechanisms. Impaired learning and memory deterioration are cognitive dysfunctions often associated with a plethora of neurodegenerative diseases, including Alzheimer’s disease. Through better understanding of the epigenetic mechanisms underlying these dysfunctions, new epigenomic therapeutic targets, such as histone deacetylases, are being explored. Here we review the intricate packaging of DNA in eukaryotic cells, and the various modifications in epigenetic mechanisms that are now linked to the neuropathology and the progression of Alzheimer’s disease (AD), as well as potential therapeutic interventions.